2007
DOI: 10.1128/iai.01479-06
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathogenic Escherichia coli , Shigella flexneri , and Listeria monocytogenes Recruit a Junctional Protein, Zonula Occludens-1, to Actin Tails and Pedestals

Abstract: Enteropathogenic Escherichia coli, Shigella flexneri, and Listeria monocytogenes induce localized actin polymerization at the cytoplasmic face of the plasma membrane or within the host cytoplasm, creating unique actin-rich structures termed pedestals or actin tails. The process is known to be mediated by the actin-related protein 2 and 3 (Arp2/3) complex, which in these cases acts downstream of neural Wiskott-Aldrich syndrome protein (N-WASP) or of a listerial functional homolog of WASP family proteins. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…5G and H; yellow pedestals). This was recently reported by Hanajima-Ozawa et al (15), who showed recruitment of ZO-1 into pedestals caused by a human EPEC strain. Moreover, cells infected with the wild type transformed with pespF showed pedestals bigger than those seen in cells infected with the untransformed wild type (Fig.…”
Section: Resultsmentioning
confidence: 51%
“…5G and H; yellow pedestals). This was recently reported by Hanajima-Ozawa et al (15), who showed recruitment of ZO-1 into pedestals caused by a human EPEC strain. Moreover, cells infected with the wild type transformed with pespF showed pedestals bigger than those seen in cells infected with the untransformed wild type (Fig.…”
Section: Resultsmentioning
confidence: 51%
“…L. monocytogenes infection is known to reduce the TEER of epithelial monolayers (33), as also observed in this study (Table 2), which can contribute to paracellular bacterial translocation (15,27). Although the exact mechanism for a Listeriainduced reduction in TEER is unknown, it has been linked to virulence traits such as actin cytoskeleton disruption following invasion (26,52,60), as well as extracellular secretion of LLO (50). Although the presence or absence of LAP expression did not induce changes in TEER (Table 2), it is possible that a weakened epithelial barrier facilitates LAP-Hsp60-mediated bacterial translocation.…”
mentioning
confidence: 54%
“…In contrast, our findings indicate an opposite sequence of events, where bacteria enter into infected eukaryotic cells to induce changes in intercellular junctions by altering signal transduction pathways. A similar sequence of events has also been described for other invasive pathogens (38), but contrasts with Helicobacter pylori infection, which is reported to alter the physiology of apical junctional complexes without entering into the cytoplasm (39).…”
Section: Discussionmentioning
confidence: 94%